Agents of change—together: Using agent-based models to inspire social capital building for resilient communities. Issue 2 (15th March 2019) - Shenk, Linda; Krejci, Caroline; Passe, Ulrike
ABSTRACT: Increasingly, civic leaders and community developers are harnessing the power of computational technologies to foster more resilient and equitable communities. This article examines how one such technology—agent-based modeling (ABM)—is well-suited not only for its use in planning and policymaking but also for inspiring the bonding, bridging, and linking social capital crucial for community resilience. ABM enables researchers and stakeholders to explore scenarios in which individual agents make choices and also interact, learn from one another, and collaborate. This article describes a case study with three groups of middle-school youth from resource-vulnerable neighborhoods in Des Moines, Iowa. Results suggest that neighborhood-scale ABMs support the adaptive systems thinking, social capital building, and collaborative action useful in contributing to long-term goals for community resilience.